2022
DOI: 10.3390/s22114036
|View full text |Cite
|
Sign up to set email alerts
|

Non-Intrusive Load Monitoring of Buildings Using Spectral Clustering

Abstract: With widely deployed smart meters, non-intrusive energy measurements have become feasible, which may benefit people by furnishing a better understanding of appliance-level energy consumption. This work is a step forward in using graph signal processing for non-intrusive load monitoring (NILM) by proposing two novel techniques: the spectral cluster mean (SC-M) and spectral cluster eigenvector (SC-EV) methods. These methods use spectral clustering for extracting individual appliance energy usage from the aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
1
10
0
1
Order By: Relevance
“…In ILM [8,9], each electric load is monitored by a separate sensor and the information acquired from all sensors can be centrally processed by cloud-end. While in NILM [6,7,10], only one monitor is required for each family or cell. It captures electric signals (such as voltage, current, and so on) at the commercial power input and transimits them to cloud server in which workload information of all loads are interpreted with algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…In ILM [8,9], each electric load is monitored by a separate sensor and the information acquired from all sensors can be centrally processed by cloud-end. While in NILM [6,7,10], only one monitor is required for each family or cell. It captures electric signals (such as voltage, current, and so on) at the commercial power input and transimits them to cloud server in which workload information of all loads are interpreted with algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…[6] UK-DALE [13], REDD [14], Refi [15] Small X [7] UK-DALE [13], REDD [14], Refi [15] Small X [8] Refi [15] Small X…”
Section: Dataset Usedmentioning
confidence: 99%
“…A similar approach is based on the analysis of the eigenvalue's spectrum of the Laplacian representing the network of appliances contributing to energy aggregation. It has been successfully proposed by Ghaffar et al In [8], it is shown that the robust eigenvalue evaluation algorithm allows the indirect determination of the weight of each load in the measured energy.…”
mentioning
confidence: 99%
“…These machine learning techniques are divided in supervised and unsupervised techniques [10]. In a previous study [11], authors proposed two unsupervised techniques for NILM applications; Spectral Cluster-Mean (SC-M) and Spectral Cluster-Eigen Vector (SC-EV).…”
Section: Introductionmentioning
confidence: 99%
“…Spectral Cluster-Mean (SC-M) method clusters data on the basis of the mean value of device power signature [11]. A linear similarity graph is defined with consecutive nodes connected and others unconnected with weights defined according to the adjacency matrix;…”
Section: Introductionmentioning
confidence: 99%